2017
DOI: 10.1002/prot.25302
|View full text |Cite
|
Sign up to set email alerts
|

Altered dynamics upon oligomerization corresponds to key functional sites

Abstract: It is known that over half of the proteins encoded by most organisms function as oligomeric complexes. Oligomerization confers structural stability and dynamics changes in proteins. We investigate the effects of oligomerization on protein dynamics and its functional significance for a set of 145 multimeric proteins. Using coarse-grained elastic network models, we inspect the changes in residue fluctuations upon oligomerization and then compare with residue conservation scores to identify the functional signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Despite their coarse-grained nature, ENMs capture the overall geometry of proteins efficiently and modes from ENMs have been shown to be significantly accurate at reproducing experimental temperature factors for a number of crystal structures. 5558 All the elastic network models and fluctuations were implemented using the ‘bio3d’ package 59 in R. We specifically used two variations of elastic network models implemented in the bio3d package: the anisotropic network model (ANM) 60 and the Hinsen’s network model 61 (referred to as HNM in this paper). In the ANM, all springs between residue i and j are assumed to have the same stiffness (spring constant ) whereas in the HNM, springs between sequentially adjacent C α atoms are represented as and those between non-adjacent C α atoms as where is the distance between residues and ; and and are constants as previously discussed.…”
Section: Methodsmentioning
confidence: 99%
“…Despite their coarse-grained nature, ENMs capture the overall geometry of proteins efficiently and modes from ENMs have been shown to be significantly accurate at reproducing experimental temperature factors for a number of crystal structures. 5558 All the elastic network models and fluctuations were implemented using the ‘bio3d’ package 59 in R. We specifically used two variations of elastic network models implemented in the bio3d package: the anisotropic network model (ANM) 60 and the Hinsen’s network model 61 (referred to as HNM in this paper). In the ANM, all springs between residue i and j are assumed to have the same stiffness (spring constant ) whereas in the HNM, springs between sequentially adjacent C α atoms are represented as and those between non-adjacent C α atoms as where is the distance between residues and ; and and are constants as previously discussed.…”
Section: Methodsmentioning
confidence: 99%
“…Each amino acid in GNM is represented by its alpha carbon and the interacting amino acid pairs are connected using hypothetical Hookean springs [15]. Previously, elastic network models have been shown to capture the near-native dynamics of proteins [16] and have been used to efficiently identify functional sites in proteins [17,18]. GNM has been previously employed to study changes in protein dynamic communities upon mutations and has been shown to possess the ability to identify stabilizing and destabilizing mutations in proteins [19].…”
Section: Introductionmentioning
confidence: 99%
“…Such interactions can lead to the creation of new functional interfaces in bound complexes, which can act as active sites or lead to increased thermal stability of the complex , compared to the isolated subunits. Moreover, the dynamics of the individual binding partners may be altered, allowing for new conformational ensembles to be sampled. Consequently, an important outcome of such interactions is the ability of a complex to orchestrate novel molecular functions often not possible by the monomeric forms .…”
Section: Introductionmentioning
confidence: 99%